2009
DOI: 10.1080/10611860902929832
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral infection or deferoxamine? Two approaches to overexpress VEGF in β-cell lines

Abstract: Rapid and adequate revascularization of transplanted islets is important for their survival and function during transplantation. Vascular endothelial growth factor (VEGF) could play a critical role with respect to islet revascularization. The aim of this study was to compare two strategies that are used to overexpress VEGF in beta-cells: (1) gene therapy through adenoviral infection and (2) a pharmacological approach using deferoxamine (DFO). beta-Cell lines from rat insulinoma (RINm5F) were either infected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…Although HGF is known to be a β-cell protector factor [29], the similar serum HGF levels found 3 days after two-thirds hepatectomy in our study did not support the role of HGF in the maintained RIN-m5F viability. In vitro, VEGF improves RIN-m5F viability [30]. In our study, a trend to the increased VEGF serum concentrations suggest that VEGF secretion following two-thirds hepatectomy would partly impact liver regeneration.…”
Section: Endocrine Researchsupporting
confidence: 54%
“…Although HGF is known to be a β-cell protector factor [29], the similar serum HGF levels found 3 days after two-thirds hepatectomy in our study did not support the role of HGF in the maintained RIN-m5F viability. In vitro, VEGF improves RIN-m5F viability [30]. In our study, a trend to the increased VEGF serum concentrations suggest that VEGF secretion following two-thirds hepatectomy would partly impact liver regeneration.…”
Section: Endocrine Researchsupporting
confidence: 54%
“…Western blotting was performed as described previously [ 16 ] using the appropriate primary and secondary antibodies: anti-rat HIF-1α mouse monoclonal antibody (R&D Systems, Minneapolis, USA; 1/1000); anti-rat mTOR and phosphorylated mTOR (Ser2448) rabbit polyclonal antibodies (Cell Signalling, Ozyme, St Quentin Yvelines, France; 1/500); anti-mouse goat peroxidase (HRP)-conjugated and anti-rabbit goat peroxidase (HRP)-conjugated antibodies (Sigma-Aldrich, St Louis, MO, USA; 1/8000). Proteins were visualized with the Luminata ™ Forte Western HRP Substrate (Millipore) and detected using enhanced chemilumiscence (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a pharmacological approach to increase VEGF expression may be more suitable for clinical application. We previously reported that pre-treatment of pancreatic islets with deferoxamine, an iron chelator already in clinical use, induced VEGF overexpression by activating the hypoxia inducible factor-1α (HIF-1α) pathway; this approach improved metabolic control in diabetic rats [ 14 ], [ 16 ]. However, long-term maintenance of graft function was not achieved, probably due to the stabilisation of HIF-1α, which triggers apoptosis at high concentrations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of ERK1/2 seems to be involved with the increase of Bcl2 mRNA and protein content, as well as the inactivation of caspase-3, mediated by an enhanced CREB expression (11). In islets from TRE5ϫ rats, we also found a significant decrease in the Bax/Bcl-2 ratio, a well known predictor of ␤-cell survival (20,25). This observation agrees with the previous description of reduced ␤-cell apoptosis in islets from trained rats (8) and provides evidence that endurance training improves ␤-cell survival through the activation of the AKT and ERK1/2 signaling pathways.…”
Section: Discussionmentioning
confidence: 58%